ANTICOCCIDIAL EFFECT OF SOME NATURAL PRODUCTS IN EXPERIMENTALLY INDUCED EIMERIA SPP. INFECTION ON CARCASS QUALITY, INTESTINAL LESION AND ILEAL HISTOLOGY IN BROILERS - Alaeldein M. Abudabos; Abdullah H. Alyemni; Elsayed O. S. Hussein; Mu’ath Q. Al-Ghadi (Journal of Animal and Plant Sciences, 2018)
We evaluated some natural products to compare their effects against a synthetic anticoccidial drug in an induced Eimeria spp. infection in broiler during the finisher stage. On day 15, a total of 200 birds (Ross 308) were randomly distributed into 10 treatments. Birds were infected with Eimeria spp. in the positive control and treatment groups. The results indicated that feed intake, body weight and feed conversion ratio (FCR) did not differ significantly (P>0.05) between synthetic anticoccidial drug and natural products. Challenged birds had longer small intestines and heavier liver as compared to unchallenged birds. Lesion score and oocysts secretion increased significantly (P<0.05) in the challenged birds, however, synthetic anticoccidial drug had no significant (P>0.05) difference with the natural products. It was concluded from the present study natural products are very effective in comparison with anticoccidial drug to control coccidiosis in broiler chicken.
Keywords: coccidiosis; broiler; drugs; natural products; control